2011
DOI: 10.3109/2000656x.2011.613649
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic rectosigmoid flap vaginoplasty

Abstract: Various methods have been developed for vaginoplasty, of which the rectosigmoid flap has its own advantages including sufficient increase in the vaginal length and lower incidence of complications such as contracture or strain after vaginoplasty. Laparoscopic operation can greatly minimise the abdominal scar associated with laparotomy and allow cosmetically superior outcomes. Its minimally invasive procedure can also achieve rapid recovery and shorten the duration of hospital stay. Twelve patients (age range 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…19 In 2011, Kim et al reported that 6 and 12 months postoperation, the sigmoid neovaginal pH level was 6.5 and 6, and squamous transformation of columnar epithelium was observed in only one of the 12 patients. 20 Predisposing factors for bowel-related complications in sigmoid vaginoplasty are tension over the vascularized pedicle, short mesentery, obesity, and masculinized pelvis; therefore, surgeons should be highly skilled. 21 We had a small intraoperative complication in only one patient whose rectum was inadvertently opened, which was diagnosed and repaired immediately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In 2011, Kim et al reported that 6 and 12 months postoperation, the sigmoid neovaginal pH level was 6.5 and 6, and squamous transformation of columnar epithelium was observed in only one of the 12 patients. 20 Predisposing factors for bowel-related complications in sigmoid vaginoplasty are tension over the vascularized pedicle, short mesentery, obesity, and masculinized pelvis; therefore, surgeons should be highly skilled. 21 We had a small intraoperative complication in only one patient whose rectum was inadvertently opened, which was diagnosed and repaired immediately.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Kim et al reported that 6 and 12 months postoperation, the sigmoid neovaginal pH level was 6.5 and 6, and squamous transformation of columnar epithelium was observed in only one of the 12 patients 20 …”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Kim et al reported that 6 and 12 months post operation, sigmoid neovaginal pH was 6.5 and 6, and squamous transformation of columnar epithelium was observed in only one of the 12 patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…Sigmoid cervicovaginoplasty is a safe and effective procedure with satisfactory outcomes during long term followups. This surgery eliminates the psychological burden of hysterectomy in these patients and if it is done by laparoscopy, patients will bene t from the advantages of minimally invasive procedures such as cosmetics (open surgery requires at least 12 to 15 cm of incision) [20], less adhesion formation, lower infection rate and wound complications, ileus, and accelerated recovery time [17]. By preserving the uterus, we can make future pregnancy possible by performing abdominal cerclage in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive techniques to create a neovagina have been developed gradually and some results have been published [ Table 1 ]. [ 4 5 6 7 8 9 10 ] Now days, these surgeries are increasingly being done with robotic assistance. The three-dimensional view with depth perception is remarkable.…”
Section: Discussionmentioning
confidence: 99%